Discovery of mechanisms of herbicide resistance using the liverwort Marchantia polymorpha - Casey, CAL (2022)
Non-target site resistance (NTSR) to herbicides in weeds is a threat to global crop yields. Few specific alleles conferring NTSR have been identified, only two of which involve loss of gene function. Here, I show that the mechanism of NTSR to the herbicide thaxtomin A (TXTA) conferred by loss-of-function of the gene PAM16 is conserved in Marchantia polymorpha, validating its use as a species with which to study NTSR. To identify novel NTSR mechanisms, I used forward genetics in M. polymorpha to generate 13 TXTA-resistant mutants and identified candidate NTSR-conferring SNPs in these mutants via mapping-by-sequencing. I identified a novel mechanism of NTSR to TXTA conferred by loss-of-function of the gene RAD8. To functionally characterise this mechanism, I generated rad8 loss-of-function mutants and found that they are cross-resistant to isoxaben, overproduce reactive oxygen species, and produce less of a putative TXTA metabolite than wild-type. I also found 4 candidate resistance-conferring SNPs in M. polymorpha homologues of genes associated with NTSR in the weed Amaranthus tuberculatus. These results demonstrate that forward genetics in M. polymorpha can identify novel NTSR alleles and corroborate existing candidate NTSR alleles, and that reverse genetics in M. polymorpha can be used to functionally characterise these resistance mechanisms.